(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Transgenders constitute quite a sizeable population that remains a neglected group, facing much discrimination from the society in many respects especially in health. With their low self esteem and suicidal tendencies owing to neglect and shaming, financial constraints, they often neglect to maintain good personal hygiene. One such component is their oral health which is in a pitiful state. With this study we aim to assess the various factors that act as barriers to the transgender community obtaining quality dental care. Their healthcare access should be much more widened with their comfortable way of acceptance.